The Effectiveness of Development Results of Pro-show Media Based on Solar System Poem and Song on Student Learning Outcomes - Yeni Kurniawanti; Budiyono Saputro; Sakshi Bahuguna (Yayasan Keluarga Guru Mandiri, 2020)
The purpose of this study was to determine the effectiveness of the results of the development of poem and song-based proshow media on MI Al-Falah Soropadan District of Pringsurat students' learning outcomes in the solar system material. The research method used is quantitative with One-Group Pretest-posttest design. The subjects of the study were sixth graders of MI AL-Falah Soropadan and teachers in Pringsurat District. The research instruments were pretest and posttest of solar material. T-test results obtained t -73.676, p = 0.00 0.05, which means that the poem and song-based proshow media development results are effective on MI Al-Falah Soropadan Pringsurat District students' learning outcomes in solar system material. Poem and song-based proshow media provide solutions for teachers and students in increasing mastery of science subjects.